2017
DOI: 10.9745/ghsp-d-17-00177
|View full text |Cite
|
Sign up to set email alerts
|

National Assessment of Data Quality and Associated Systems-Level Factors in Malawi

Abstract: Nearly all facility registers were available and complete. But accuracy varied, with antenatal care and HIV testing and counseling performing the best and family planning and acute respiratory infections data less well. Most facilities visibly displayed routine health data and most hospitals and district health offices had staff trained in health management information systems, but training was lacking at the facility level as were routine data quality checks and regular supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 12 publications
4
63
1
Order By: Relevance
“…We found that the cost per mobile interview was $10.56 (or 7655 Kwacha), while the cost per in-person interview was $25.48 (18,473 Kwacha). One of the largest drivers of cost in the mobile interview phase stemmed from the airtime used.…”
Section: Feasibilitymentioning
confidence: 81%
See 1 more Smart Citation
“…We found that the cost per mobile interview was $10.56 (or 7655 Kwacha), while the cost per in-person interview was $25.48 (18,473 Kwacha). One of the largest drivers of cost in the mobile interview phase stemmed from the airtime used.…”
Section: Feasibilitymentioning
confidence: 81%
“…While health systems usually collect routine data on FP provision that could be used for an ISA, a common challenge is the poor quality of this data at the national and subnational levels [18][19][20]. Another option is collecting primary data on program implementation from each of these health system actors, but the traditional, in-person method can be labor and costintensive.…”
Section: Introductionmentioning
confidence: 99%
“…3 Despite substantial investment of time and resources in the DHS programme worldwide, the quality of data arising from these surveys has been variable. 4 Few research studies have attempted to uncover the underlying reasons for this variation 5 and, to date, no randomised trials (the gold standard for research) have been done to improve DHS methodology.…”
Section: Enhancing Routine Surveillance To Improve Stillbirth Datamentioning
confidence: 99%
“…Studies in Sub-Saharan Africa (SSA) have reported challenges with data quality, including poor utilization of HMIS tools, incomplete recording, inconsistency, inaccuracy and untimely reporting [1,[5][6][7][8][9][10][11][12][13]. The concerns about the quality of routine information have undermined data utilization for decision-making in the health sector [9,10,14,15]. Challenges in data quality in SSA are compounded by human, health system (HS) and infrastructure factors [1,2,16].…”
Section: Introductionmentioning
confidence: 99%
“…Limited infrastructure and means to transmit reports from one level to another add more complexity [5,14,[17][18][19]. Data quality assessments need to address these attributes and processes to establish valid conclusions that foster solution-focused thinking [15,16].…”
Section: Introductionmentioning
confidence: 99%